JNJ‐4178 (AL‐335, Odalasvir, and Simeprevir) for 6 or 8 Weeks in Hepatitis C Virus‐Infected Patients Without Cirrhosis: OMEGA‐1. Issue 6 (14th March 2019) - Zeuzem, Stefan; Bourgeois, Stefan; Greenbloom, Susan; Buti, Maria; Aghemo, Alessio; Lampertico, Pietro; Janczewska, Ewa; Lim, Seng Gee; Moreno, Christophe; Buggisch, Peter; Tam, Edward; Corbett, Chris; et al.
Abstract : The combination of three direct‐acting antiviral agents (AL‐335, odalasvir, and simeprevir: JNJ‐4178 regimen) for 6 or 8 weeks demonstrated good efficacy and safety in a phase IIa study in chronic hepatitis C virus (HCV) genotype (GT)‐1‐infected patients without cirrhosis and has now been evaluated in a larger phase IIb study, OMEGA‐1. This multicenter, randomized, open‐label study (NCT02765490) enrolled treatment‐naïve and interferon (±ribavirin) treatment‐experienced patients with HCV GT1, 2, 4, 5, or 6 infection. Patients with HCV GT3 infection and/or liver cirrhosis were excluded. Patients received AL‐335 800 mg, odalasvir 25 mg, and simeprevir 75 mg once daily for 6 or 8 weeks. The primary endpoint was sustained virologic response 12 weeks after the end of treatment (SVR12). In total, 365 patients (GT1a, 29.3%; GT1b, 42.5%; GT2, 12.3%; GT4, 14.2%; GT5, 1.4%; GT6, 0%) were randomized to receive 6 weeks (n = 183) or 8 weeks (n = 182) of treatment. SVR12 rates after 6 weeks (98.9%) or 8 weeks (97.8%) of treatment were noninferior to a historical control (98%). Viral relapse occurred in 5 patients (1.4%; 4 with HCV GT2c; 1 with GT1a). With the exception of 4 patients in the 8‐week group, including 3 patients with missing data at the SVR24 timepoint, all patients who achieved SVR12 also achieved SVR24. One GT1a‐infected patient experienced late viral relapse after achieving SVR18. Most adverse events (AEs) were mild with no treatment‐related serious AEs. All randomized patients completed treatment. Conclusion: In HCV‐infected patients, 6 and 8 weeks of treatment with JNJ‐4178 resulted in SVR12 rates of 98.9% and 97.8%, respectively, and was well tolerated.